Fluorescence measurements of the marine flatworm Macrostomum lignano during exposure to TNT and its derivatives 2-ADNT and 4-ADNT. (October 2020) - Bickmeyer, Ulf; Meinen, Ina; Meyer, Stefanie; Kröner, Svenja; Brenner, Matthias
Abstract: Fluorescence measurements of the marine flatworm Macrostomum lignano were performed during exposure to the explosive TNT and its main derivatives 2-ADNT and 4-ADNT, using calcein AM, the acetoxymethylester of calcein, and the autofluorescence of its food (diatoms). Lethality was found to depend on temperature and exposure time. After 12 days of exposure to a concentration of 33, 3 mg/L 2-ADNT and 4-ADNT, the lethality at 30 °C (100%) was strongly increased compared to 21 °C (~60%). First deaths were observed after four days of exposure. Using lower concentrations (≤3, 33 mg/L) of all three compounds, the activity of ABC transporters (ATP binding cassette transporter) was determined using calcein as reporter dye. Worms exposed to toxicants for 72 h showed a significant upregulation of ABC transporter activity during exposure to 3, 33 mg/L 2-ADNT and 4-ADNT, and 3 mg/L TNT demonstrating the efficacy of this cellular first line defense. A distinct behavioral defense of the worms decreased the uptake of 2-ADNT and 4-ADNT (0, 033 mg/L) as they reduced feeding shown by diminished autofluorescence of algae in the gut. Graphical abstract: Image 1 Highlights: Reduced feeding as behavioral defense against uptake of toxicants. Lethality of 2-ADNT and 4-ADNT is time and temperature dependent. ABCC transporter are upregulated in the presence of 2-ADNT, 4-ADNT and TNT.